Nursing of Babylon Snail (Babylonia areolata Link, 1807) from Veliger Larvae to Early Juveniles Using Different Materials Attached on Edge of Nursing Tanks for Prevention of Crawling Out - Parinya Sutthinon,; Wara Taparhudee,; Renu Yashiro, (Agriculture and Natural Resources, 2007)
Nursing of Babylon snail (Babylonia areolata Link, 1807), from veliger larvae to 60 days old early juveniles using different materials attached on the edge of the nursing tank to prevent the juveniles crawling out from the tank was conducted at Rayong Coastal Fisheries Research and Development Center. Five treatments with five replications were set up for the experiment (T1-T5), T1 : control treatment (no material); T2 : thick plastic sheet; T3 : thin plastic sheet; T4 : nylon net sheet and T5 : foam rubber sheet. The average final shell length of Babylon snail in five treatments was 12.16 ± 0.93, 9.43 ± 0.35, 9.83 ± 0.47, 8.47 ± 0.40 and 10.99 ± 0.31 mm, respectively. The average survival rates were 1.22 ± 0.51, 13.38 ± 0.61, 10.14 ± 0.60, 21.58 ± 2.43 and 6.45 ± 1.10 %, respectively. The average final shell length and the average survival rates of all treatments were significantly different at p<0.05. Nylon net sheet is the best material for preventing the juveniles crawling out from the nursing tank.